2018
DOI: 10.1002/bse.2207
|View full text |Cite
|
Sign up to set email alerts
|

Social capital and firms' environmental innovations: The moderating role of environmental scanning

Abstract: Seen as an effective way to balance financial and environmental goals, environmental innovation has become a priority for firms. Based on the theory of social capital, this study examined the antecedents of firms' environmental innovations. Selecting environmental scanning as the moderator, this study analyzed the relationship between the three dimensions of social capital and environmental innovation. Two hundred and forty firms in the manufacturing industry were selected as the sample, and the data were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(109 citation statements)
references
References 45 publications
8
98
0
3
Order By: Relevance
“…Consistent with the tenets of social capital theory, the main findings offer strong empirical evidence on the critical role played by a firm's external linkages, relationships and networks in augmenting a firm's available resources that can be allocated to EM. Consistent with previous studies (e.g., Eklinder-Frick, Eriksson, & Hallén, 2014;Liao, 2018;Sahasranamam & Nandakumar, 2020) that highlight the role of social capital in the performance of SMEs, the current findings support the argument that social capital enables firms to gain access to physical resources such as technology and machinery essential in EM (Canevari-Luzardo, Berkhout, & Pelling, 2020;Hofmann, Theyel, & Wood, 2012 Fynes, 2020;Poon, Thai, & Naybor, 2012) by demonstrating that there is an empirically grounded and strong link between social capital and SME's pursuit for EM initiatives. The SME-focused measurement of social capital (concerning environmental sustainability) followed in this study fills the gap identified in previous studies, which used measures that were either distant from the context of SMEs in transition or developing economies (e.g., Liao, 2018) or too generic, qualitative and limited in scope (e.g., Calza, Parmentola, & Tutore, 2020;Canevari-Luzardo et al, 2018;Hoffmann et al, 2012) to capture the nuanced elements of social capital (or its related concepts such as…”
Section: Discussion Of the Findingssupporting
confidence: 89%
“…Consistent with the tenets of social capital theory, the main findings offer strong empirical evidence on the critical role played by a firm's external linkages, relationships and networks in augmenting a firm's available resources that can be allocated to EM. Consistent with previous studies (e.g., Eklinder-Frick, Eriksson, & Hallén, 2014;Liao, 2018;Sahasranamam & Nandakumar, 2020) that highlight the role of social capital in the performance of SMEs, the current findings support the argument that social capital enables firms to gain access to physical resources such as technology and machinery essential in EM (Canevari-Luzardo, Berkhout, & Pelling, 2020;Hofmann, Theyel, & Wood, 2012 Fynes, 2020;Poon, Thai, & Naybor, 2012) by demonstrating that there is an empirically grounded and strong link between social capital and SME's pursuit for EM initiatives. The SME-focused measurement of social capital (concerning environmental sustainability) followed in this study fills the gap identified in previous studies, which used measures that were either distant from the context of SMEs in transition or developing economies (e.g., Liao, 2018) or too generic, qualitative and limited in scope (e.g., Calza, Parmentola, & Tutore, 2020;Canevari-Luzardo et al, 2018;Hoffmann et al, 2012) to capture the nuanced elements of social capital (or its related concepts such as…”
Section: Discussion Of the Findingssupporting
confidence: 89%
“…Companies are facing increasingly competitive and uncertain business environments, changing consumer preferences, and continuous pressure to innovate (Chavez, Yu, Jacobs, & Feng, 2017; Liao, 2018; Wang, Cai, Liang, Wang, & Xiang, 2018; Thi Mai Anh, Hui, Khoa, & Mehmood, 2019). Many companies invest resources to innovate by applying internal knowledge, as well as by leveraging external intelligence from the supply chains (SCs) within which they operate.…”
Section: Introductionmentioning
confidence: 99%
“…Bazı araştırmalarda iş karmaşıklığının, iş performansı, iş tatmini ve işe katılım gibi işle ilgili sonuçlarla pozitif bağlantılı olduğunu bulmuşlardır (Becton vd., 2017). Diğer çalışmalarda ise, yüksek karmaşıklığa sahip işlerin "baskıyı" ve "işle ilgili talepleri" artırabileceğini öne sürmüştür (Janssen, 2001 (Liao, 2018). (Guler vd., 2002).…”
Section: İş Karmaşıklığıunclassified
“…Ayrıca firmaların keşifsel pazar yönelimleri, yönetim yeniliğini benimsemelerini kolaylaştırabilmektedir. Keşifsel pazar yönelimi, firmaların kapsamlı çevre analizi yapmalarına ve diğer firmalar tarafından uygulanan yenilikçi yönetim araç ve tekniklerini benimsemelerine de yardımcı olmaktadır (Liao, 2018).…”
Section: 1unclassified
See 1 more Smart Citation